The effect of grasp compatibility in go/no-go and two-choice tasks. - Pecher, Diane; Roest, Sander; Zeelenberg, René (Memory & Cognition, 2019)
The grasp compatibility effect has been put forward as evidence for the automatic involvement of the motor system during mental object representation. In three experiments, participants responded to object pictures or names by grasping cylinders using a precision or power grasp. In a two-choice task in which both grasps were used, we obtained grasp compatibility effects, but in a go/no-go task, in which only one grasp was used, there was no effect. These results indicate that the effect depends on the availability of response choice, in the present case, different size grasps. This suggests that grasp compatibility effects are better explained by coding of the stimulus and response on the same dimension, size, rather than automatic activation of a motor action towards the object.